Raupenfliegen aus der Umgebung von Magdeburg (Diptera, Tachinidae). - Ziegler, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1993)
Ecological and faunistical data are compiled for 149 tachinid flies (Diptera, Tachinidae) found in the environs of Magdeburg (Germany) between 1981 and 1992. Graphogaster nigrescens and Ramonda prunicia are new for the German fauna.